1992
DOI: 10.1098/rstb.1992.0065
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that adaptation of suppression cannot account for auditory enhancement or enhanced forward masking

Abstract: Delaying the onset of a signal relative to the onset of a simultaneous notched masker often improves the ability of listeners to 'hear out' the signal at both threshold and suprathreshold levels. Viemeister & Bacon (J. acoust. Soc. Am., 71, 1502-1507 (1982)) suggested that such auditory enhancement effects could be accounted for if the suppression produced by the masker on the signal frequency adapted, thereby releasing the signal from suppression. In support of their hypothesis, Viemeister & Bacon reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Viemeister and Bacon [5] found that enhancing a target tone increases its forward masking of a subsequent signal. This finding, replicated several times [6], [26], [27], indicates that exposure to the precursor causes an increase in the effective level of the target tone. This increase in the effective level of the target tone has been interpreted as the consequence of a reduction in the inhibition that the adapted background components would exert on the target tone (adaptation of inhibition hypothesis).…”
Section: Discussionmentioning
confidence: 57%
“…Viemeister and Bacon [5] found that enhancing a target tone increases its forward masking of a subsequent signal. This finding, replicated several times [6], [26], [27], indicates that exposure to the precursor causes an increase in the effective level of the target tone. This increase in the effective level of the target tone has been interpreted as the consequence of a reduction in the inhibition that the adapted background components would exert on the target tone (adaptation of inhibition hypothesis).…”
Section: Discussionmentioning
confidence: 57%
“…In the above mentioned studies, frequency discrimination involves presentation of multiple tones separated by short durations (300~350 ms) of silence. The forward masking effect between sequential tones ( (Harris and Dallos, 1979;McFadden and Wright, 1987;Wright and McFadden, 1992;Calford and Semple, 1995;Brosch and Schreiner, 1997;Tai and Zador, 2002;Wehr and Zador, 2005)) also has to be considered in addition to any attentional manipulation one would like to study using these paradigm.…”
Section: Two-tone Discrimination Behavior In Ratsmentioning
confidence: 99%